The Effect of Application of Mycorhyza and Inorganic Fertilizers on The Growth of Palm Seedlings in Pre and Main Nursery - Istiqomah, Fatimah Nur; Novanto, Praditya Rizqi; Janati, Rahayu Ning (Jurnal Penelitian Kelapa Sawit, 2025)
Fertilization is one of the factors that affect oil palm productivity. Three types of fertilizers are commonly used for oil palm cultivation, namely organic, inorganic, and biological. One type of biological fertilizer is mycorrhiza, a fertilizer made from fungi. This study aims to determine the role of mycorrhiza and various doses of NPK fertilizer on the vegetative growth of oil palm seedlings. The research method in the pre-nursery used a completely randomized design (CRD) with treatments; control (A), 100% NPK fertilizer (B), 30 g mycorrhiza (C), 30 g mycorrhiza + 25% NPK fertilizer (D), 30 g mycorrhiza + 50% NPK fertilizer (E) 30 g mycorrhiza + 75% NPK fertilizer with 25 replications. The research method in the main nursery used a completely randomized design (CRD) with treatments: control (A), 100% NPK fertilizer (B), 40 g mycorrhiza (C), 40 g mycorrhiza + 25% NPK fertilizer (D), 40 g mycorrhiza + 50% NPK fertilizer (E) 40 g mycorrhiza + 75% NPK fertilizer with 20 repetitions. The results showed that the application of 30 g mycorrhiza to pre-nursery oil palm seedlings could increase seedling height by 73.75% better than the control, and the application of 30 g mycorrhiza + 50% NPK fertilizer could increase seedling height by 59.57%. Applying 40 g mycorrhiza + 75% NPK fertilizer could increase height by 71.97% and diameter by 54.26% compared to the control in main-nursery oil palm seedlings. The application of 30 g of mycorrhiza in the pre-nursery can increase the efficiency of NPK fertilizer by 50%, and the application of 40 g of mycorrhiza in the main nursery can increase the efficiency of NPK fertilizer by 25%.